Transient Auditory Neuropathy with Resurgence of Electrophysiological Waveforms Observed between the Neonatal Period and Age 3 Years - Evans, Adele K.; Baudoin, Morgan E.; Knight, Haley E.; Giles, Amanda (Journal of the American Academy of Audiology, 2023)
Auditory neuropathy spectrum disorder (ANSD) is a spectrum of conditions marked by diminished auditory function and believed to be caused by the impaired neural transmission of auditory stimulation in the setting of functional outer hair cells. There are reports of “spontaneously resolving” or “transient” ANSD (transient auditory neuropathy [TAN]) in the literature. In this case report of TAN, we demonstrate the resurgence of the auditory brainstem response waveform morphology over a 3-year period to reveal electrophysiological testing consistent with the patient's functional hearing level by age 3 years.
Keywords: auditory neuropathy; universal newborn hearing screen; spontaneous recovery; waveforms; auditory brainstem response testing